2017
DOI: 10.1186/s13104-017-2897-x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia in type 2 diabetic model KK-Ay/Ta mice: a potent animal model with positive correlation between insulin resistance and plasma high uric acid levels

Abstract: ObjectiveHyperuricemia is recognized as a main cause of gout. Accumulating clinical evidence suggests that hyperuricemia is strongly associated with insulin resistance and abnormal glucose metabolism. However, there seem no proper animal models for investigating such associations. Ideal animal model is considered to be hyperuricemic as well as diabetic. Selecting the KK-Ay/Ta mouse model, the relationship between hyperuricemia and insulin resistance has been studied to characterize such an animal model.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 29 publications
3
15
0
Order By: Relevance
“…Plasma triglyceride and total cholesterol levels were significantly elevated in the diabetic state (CNT) compared with those in the normal state (NOR), but these elevations were not significantly suppressed (p < 0.1) by oral administration of taxifolin (TXF) (Figure 5A,B). The plasma uric acid level was significantly higher in the diabetic state (CNT) than in the normal state (NOR), confirming the occurrence of hyperuricemia in T2D model KK-A y /Ta mice as previously reported [19], and TXF was found to significantly suppress this hyperuricemia (Figure 5C) as well as hyperglycemia (Figure 4B). In contrast, adiponectin, which is known to activate muscle AMPK [27], significantly decreased in T2D model KK-A y /Ta mice (CNT) in comparison with normal ones (NOR), and TXF administration exerted no influence on this reduction (TXF) (Figure 5D).…”
Section: In Vivo Effect Of Taxifolin On Plasma Glucose Insulin and Homa-ir In T2d Model Micesupporting
confidence: 90%
See 2 more Smart Citations
“…Plasma triglyceride and total cholesterol levels were significantly elevated in the diabetic state (CNT) compared with those in the normal state (NOR), but these elevations were not significantly suppressed (p < 0.1) by oral administration of taxifolin (TXF) (Figure 5A,B). The plasma uric acid level was significantly higher in the diabetic state (CNT) than in the normal state (NOR), confirming the occurrence of hyperuricemia in T2D model KK-A y /Ta mice as previously reported [19], and TXF was found to significantly suppress this hyperuricemia (Figure 5C) as well as hyperglycemia (Figure 4B). In contrast, adiponectin, which is known to activate muscle AMPK [27], significantly decreased in T2D model KK-A y /Ta mice (CNT) in comparison with normal ones (NOR), and TXF administration exerted no influence on this reduction (TXF) (Figure 5D).…”
Section: In Vivo Effect Of Taxifolin On Plasma Glucose Insulin and Homa-ir In T2d Model Micesupporting
confidence: 90%
“…Plasma triglyceride and total cholesterol levels were si icantly elevated in the diabetic state (CNT) compared with those in the normal (NOR), but these elevations were not significantly suppressed (p < 0.1) by oral admini tion of taxifolin (TXF)(Figure 5A,B). The plasma uric acid level was significantly high the diabetic state (CNT) than in the normal state (NOR), confirming the occurrenc hyperuricemia in T2D model KK-A y /Ta mice as previously reported [19], and TXF Figure 5 shows the effect of taxifolin on the plasma levels of triglyceride (A), total cholesterol (B), uric acid (C), and adiponectin (D) 6 h after fasting at the end of the experimental period of four weeks. Plasma triglyceride and total cholesterol levels were significantly elevated in the diabetic state (CNT) compared with those in the normal state (NOR), but these elevations were not significantly suppressed (p < 0.1) by oral administration of taxifolin (TXF) (Figure 5A,B).…”
Section: In Vivo Effect Of Taxifolin On Plasma Glucose Insulin and Homa-ir In T2d Model Micesupporting
confidence: 89%
See 1 more Smart Citation
“…Although it is possible that hyperuricemia might be causative of diabetes rather than the other way around (31), the causality remains uncertain, because confounders, reverse causality, or common etiological factors might explain the epidemiological results (29). In fact, recent human and mouse data imply that diabetes increases the risk of hyperuricemia (29,32). Notably, significantly (on average >10-fold) elevated levels of d-lactate .…”
Section: Author Contributionsmentioning
confidence: 99%
“…Many studies have demonstrated a positive correlation of hyperuricemia with the risk ofT2DM. Moreover, one animal-model research has shown that the serum level of uric acid could be positively associated with insulin resistance in mice ( Adachi et al, 2017 ). An observational study showed that after adjusting for diabetic risk factors, people with a higher level of serum uric acid might have a greater risk of developing T2DM as compared to people with lower serum level of uric acid ( Sluijs et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%